Geochemistry of the Lower Protezoroic Granulite-Facies Grant Syenite Gneiss, Barra Velha, Santa Catarina State, Southern Brazil. - HARTMANN, LÉO; BASEI, MIGUEL; SIMAS, MARGARETE (Pesquisas em Geociências, 1998)
A syenite body was discovered and studied in the Santa Catarina Granulitic Complex, close to the beaches of Grant and Barra Velha. The quarry, located on km·91 of BR-101 highway, was sampled for geochemical whole rock studies and also of its individual minerals. The syenite body is in structural and metamorphic equilibrium with the containing hypersthene-bearing tonalitic and basaltic granulites. Major, trace and rare-earth elements analyses on rock samples indicate syenitic to quartz dioritic compositions, saturated in alumina and silica. They have high contents of K, Na, Sr and Ba and low contents of Zr and Ti. Total REE is high in chondrite-normalized paterns and indicates strong fractionation of the light REE, similar to those for the Itiúba Syenite from Bahia State and for the Linden Syenite from Minnesota, USA. Overall geochemistry, on the other hand, is remarkably similar to the Archean Cléricy Pluton from Canada. The REE are strongly concentrated in allanite, clinopyroxene and sphene strongly. A Sm-Nd mineral isochron indicates metamorphic crystallization at ca. 2.2 Ga. The syenite is depleted in HFSE, and this may indicated a subduction-zone tectonic environment of generation of the magma. The foregoing results are based on 12 whole rock chemical analyses for major and some trace elements, three whole rock REE analyses, two electron microprobe analyses on each of seven minerals and Sm/Nd isotopic determinations on five minerals.